Ergonomic Work Station Design In Internet Rental Services At Warnet Bina Boyolali - Haryanto, Haryanto (Sean Institute, 2023)
Responding to the rapid progress of the internet and the large public need for internet service users, many internet cafes have been opened. Many internet cafes in designing their work stations are less ergonomic so that it often causes complaints for users. Therefore, it is necessary to conduct research on how to design an ergonomic work station in order to provide comfort for internet rental service users. The research was conducted at the Bina Boyolali internet cafe with the object of research regarding the size of computer tables and chairs. Computer desks and chairs are facilities provided at Bina's internet cafe. The tables and chairs used by the internet cafe operators felt uncomfortable, which was caused by the sitting position which eventually caused fatigue in the limbs. The research process begins with collecting data through a Nordic Body Map questionnaire to find out whether visitors are comfortable with the conditions of the existing work station. From the questionnaires distributed to 60 respondents, it can be seen that 1.32% of visitors felt very comfortable with the size of the table and chair size, the location of the board and the distance from the monitor to the eyes. Visitors who feel comfortable are 19.34%, those who feel quite comfortable are 42.63%, those who feel less comfortable are 34.41% and feel uncomfortable are 2.31%. This shows that the Bina Boyolali internet cafe work station is still less ergonomic so that many visitors feel uncomfortable. From the questionnaires distributed to 60 respondents, it can be seen that 1.32% of visitors felt very comfortable with the size of the table and chair size, the location of the board and the distance from the monitor to the eyes. Visitors who feel comfortable are 19.34%, those who feel quite comfortable are 42.63%, those who feel less comfortable are 34.41% and feel uncomfortable are 2.31%. This shows that the Bina Boyolali internet cafe work station is still less ergonomic so that many visitors feel uncomfortable. From the questionnaires distributed to 60 respondents, it can be seen that 1.32% of visitors felt very comfortable with the size of the table and chair size, the location of the board and the distance from the monitor to the eyes. Visitors who feel comfortable are 19.34%, those who feel quite comfortable are 42.63%, those who feel less comfortable are 34.41% and feel uncomfortable are 2.31%. This shows that the Bina Boyolali internet cafe work station is still less ergonomic so that many visitors feel uncomfortable.